PENERAPAN MODEL TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTUAN MEDIA CANVA PADA MENULIS SURAT LAMARAN PEKERJAAN KELAS XI SMK PASUNDAN 2 BANDUNG - Ayu Komalasari; Any Budiarti; Adi (STKIP Subang, 2024)
This study was motivated by the low ability of students in writing job application letters. The reason is the lack of understanding and renewal of vocabulary so that it is difficult to pour an idea into a complete writing and the use of learning models used by educators is still monotonous. One of the learning models that can be used as an alternative in writing job application letters is the Team Assisted Individualization (TAI) model. The purpose of this study was to determine the ability of students in writing job application letters before and after applying the Team Assisted Individualization (TAI) model. The research method used is an experimental method with a Quasi-Experimental Nonequivalent Control Group Design. The author compiled the research results after conducting research on students of class XI TKJ A as the experimental class and XI TKJ E as the control class. The results showed that the author was able to implement learning with the Team Assisted Individualization (TAI) model with a score of 3.8. The results of the experimental pretest scores with an average value of 56 and increased in the posttest results after applying the model with an average of 83. While the average value of the control pretest was 48.5 and increased with a value of 67. So there are results of differences between the experimental class and the control class. Supported by the output results on the Mann Whitney test of 0.000 <0.05, the hypothesis can be accepted. Based on the results of this study, the authors can conclude that the application of the Team Assisted Individualization (TAI) model assisted by Canva media in learning to write job application letters for class XI students of SMK Pasundan 2 Bandung is successful.